2018
DOI: 10.1186/s13584-018-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

The demographic and morbidity characteristics of a population receiving food support in Israel

Abstract: The nutrition and medical status of the population receiving food support is much worse than in the general population. There is a need to improve the nutritional value of food support; this could include greater emphasis on whole grains, fruits and vegetables. There is also a need for a nationwide education program to focus on healthy nutrition and to subsidize healthy foods. Many health and nutrition promotion models show that in order to effect changes in dietary habits and behaviors related to improving nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Compared to the two aforementioned studies, the remaining six studies contained less information to assess the effect of BMI on the association between FIS and selfreported previous diagnosis in hypertension. Lastly, three studies of varying methodology reported data on the association between food insecurity and hypertension without differentiating the data between adult and pediatric subjects (S2.4 Table in S2 File) [56][57][58]. The studies were not combined by meta-analyses.…”
Section: Plos Onementioning
confidence: 99%
“…Compared to the two aforementioned studies, the remaining six studies contained less information to assess the effect of BMI on the association between FIS and selfreported previous diagnosis in hypertension. Lastly, three studies of varying methodology reported data on the association between food insecurity and hypertension without differentiating the data between adult and pediatric subjects (S2.4 Table in S2 File) [56][57][58]. The studies were not combined by meta-analyses.…”
Section: Plos Onementioning
confidence: 99%
“…Data from a National Insurance Institute and Ministry of Health survey of food insecure households show that one third of surveyed households had at least one member with diet-related conditions including anemia (33%), high blood pressure (22%), diabetes (17%) and cardiovascular disease (12%). These rates are 2–3 times higher than would be expected in the general population (53). Self-reported rates of these conditions among our sample of food pantry users were even higher (Table 3).…”
Section: Discussionmentioning
confidence: 57%
“…Five studies (Alvares and Amaral, 2014; Gregório et al , 2014; Gregório et al , 2018; Maia et al , 2019a; Melo et al , 2019) took place in Portugal and the reported levels of food insecurity levels varied from 11 (Maia et al , 2019a) to 50.7% (Gregório et al , 2014). A study in Greece in a sample of 236 young adults (Theodoridis et al , 2018) and a study in Israel in a sample of 362 families (Endeweld et al , 2018), both reported that 82% of the participants, were food insecure.…”
Section: Resultsmentioning
confidence: 99%
“… For simplicity reasons the studies by Shankar-Krishnan et al (2018), Esturk et al (2014), Endeweld et al (2018), Ganhao-Arranhado et al (2018), Laurence et al (2017), Theodoridis et al (2018), Grammatikopoulou et al (2019), Dalma et al (2018), Pilot et al (2014), Baptista et al (2018) and Zamora‐Sarabia et al (2019) are not presented in this table because the sample size is less than 500 participants…”
Section: Figurementioning
confidence: 99%